2005
DOI: 10.1128/jb.187.7.2261-2266.2005
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Major Cellulosomal Endoglucanases of Clostridium thermocellum Differs from That of a Prominent Cellulosomal Xylanase

Abstract: The expression of scaffoldin-anchoring genes and one of the major processive endoglucanases (CelS) from the cellulosome of Clostridium thermocellum has been shown to be dependent on the growth rate. For the present work, we studied the gene regulation of selected cellulosomal endoglucanases and a major xylanase in order to examine the previously observed substrate-linked alterations in cellulosome composition. For this purpose, the transcript levels of genes encoding endoglucanases CelB, CelG, and CelD and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
32
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 40 publications
7
32
2
Order By: Relevance
“…The detection of CelN and CelQ on Avicel and not cellobiose may be taken as another indication of increased GH9 endoglucanase production on Avicel. The differential expression of GH9 versus GH5 endoglucanases poses an apparent discrepancy with the recent transcript analysis of Dror et al (9), who observed increased transcript levels per cell of each of the endoglucanase genes celB and celG from GH5 and celD from GH9 when cells were grown at a low versus a high growth rate and also on cellulose versus cellobiose. Thus, while our results with respect to GH9 endoglucanases agree with these previous findings at the transcript level, the increase of GH5 endoglucanases and of CelA on cellobiose was a somewhat unanticipated result.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…The detection of CelN and CelQ on Avicel and not cellobiose may be taken as another indication of increased GH9 endoglucanase production on Avicel. The differential expression of GH9 versus GH5 endoglucanases poses an apparent discrepancy with the recent transcript analysis of Dror et al (9), who observed increased transcript levels per cell of each of the endoglucanase genes celB and celG from GH5 and celD from GH9 when cells were grown at a low versus a high growth rate and also on cellulose versus cellobiose. Thus, while our results with respect to GH9 endoglucanases agree with these previous findings at the transcript level, the increase of GH5 endoglucanases and of CelA on cellobiose was a somewhat unanticipated result.…”
Section: Discussioncontrasting
confidence: 50%
“…Finally, with respect to hemicellulases, all subunits with xylanase or xyloglucanase activity decreased on Avicel, as per RelEx and emPAI analysis. XynC production has previously been shown to increase on cellobiose (4,9), and xynC transcript levels have been found to increase on cellobiose in a growth rate-independent fashion (9). In this study, XynZ, XynA, XynC, and XghA were among the five most abundant docking components in cellobiose-grown cellulosomes, along with CelA.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The expression of celS is growth rate-dependent as revealed by chemostat experiments (25,27). Similarly, the transcript levels of cipA, olpB, orf2p, celB, celG, and celD are dependent on growth rate (28,29). In contrast, the expression of sdbA and xynC are independent from growth rate.…”
mentioning
confidence: 95%
“…Thus, scaffoldin and cellulase genes have similar transcriptional responses to growth rate and substrate (10,11,37), and transcriptional regulators have been associated with some cellulase genes (22). Previously, Stevenson and Weimer conducted a real-time PCR survey of the expression of 17 C. thermocellum genes involved in cellulose hydrolysis, intracellular phosphorylation, and catabolite repression and correlated their expression profiles with the formation of fermentation products (31).…”
mentioning
confidence: 99%